Pengaruh Kepatuhan Pajak dan Literasi Keuangan terhadap Kinerja Keuangan UMKM di Kecamatan Dompu - Ninik Tri Winasis; Mahmud Mahmud; Fahrul Mauzu (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyze the influence of tax compliance and financial literacy on the financial performance of MSMEs in Dompu District. This research method applies a quantitative approach with a causal associative descriptive design. The population in this study includes all MSME actors operating in the Dompu District area as many as 1,291 by 2025. The determination of the sample of this study used the Slovin Formula with a margin of error of 10% so that a sample of 93 MSMEs was obtained in the Dompu District area. Data analysis was carried out through multiple linear regression models to test the influence of independent variables on dependent variables partially or simultaneously. The results of the study show that partially tax compliance has a positive and significant effect on the financial performance of MSMEs and the financial literacy variable has a positive and significant effect on the financial performance of MSMEs. Meanwhile, simultaneously, the variables of tax compliance and financial literacy have a positive and significant effect on the financial performance of MSMEs in Dompu District.